REKONDISI SILABUS MATAKULIAH PENDIDIKAN AGAMA ISLAM PADA PRODI DESAIN GRAFIS KONSENTRASI MULTIMEDIA POLITEKNIK NEGERI MEDIA KREATIF PSDD MEDAN - Gunawan Gunawan (UIN Sumatera Utara Medan, 2018)
In the process of making the learning syllabus is done by using an analysis of the vision and mission of the educational institutions that correlate to the moral conditions of students and look at the needs in the world of work, the process of making instructional materials is also carried out from a combination of the elaboration of the entire subject syllabus and the needs of the Industrial world followed by the development of activities religion that leads student behavior to good character. Organizational elements of students are also involved in determining the direction of moral change better, because they are in the organizational organ in the institution both in the concept and order of the campus administration, and good in dealing with the world of work and industry. Good work is seen from good character and attitude.